Introducción a la física de procesos desde una perspectiva fenomenológica - Chaparro, Clara Inés; Gonzáles, José; Orozco C, Juan Carlos; Pedreros, Rosa Inés; Vallejo, Jorge I (Revista Educación y Pedagogía, 2015)
.